Evaluasi Program Pendampingan Belajar di Luar Jam Sekolah untuk Meningkatkan Literasi dan Numerasi Siswa - Ulya, Khairatul; Ikhlas, T. Muhammad; Muarif, Alfy; Jannah, Miftahul; Triyana; Ananda, Delvia Yuka (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
Guided Learning Outside School days is an initiative program conducted to enhance grade VII students’ literacy and numeracy. This activity is conducted by a group of students guided by a lecturer of IAIN Langsa, Aceh, Indonesia as part of students’ community services program. The program aims to enhance students’ literacy and numeracy including Tahsin Al-Qur’an, Mathematics, Arabic and English subject. The activity consists of 10 students from grade VII for each subject. Data analysis show that the students’ literacy and numeracy rose about 20% of average score. Moreover, team of students’ community services could cooperate with team from school community both teachers and students as a support factor to achieve program goals. By analyzing and evaluating program, it showed that the program was categorized as a succeed program and give a high contribution for school communities to enhance students’ literacy and numeracy